Cognitive processes in problem solving: bridging the intersection of cognition and management science problems - Cheng, Sheila; Siow, Heng Loke (Florida: International Institute of Informatics and Systemics, 2011)
Decision making is vital to business and life. Management Science (MS) seems to help people make better informed decisions and thus could make a difference to the real world. However, solving MS problems need inputs from cognitive psychology and therefore require the bridging of both for a mutual coexistence. Many researchers acknowledged that decision makers are required to possess different problem solving skills to approach different types of problems, such as the solving of well-structured and ill-structured problems require peculiar cognitive processes. Insofar, there is a need for deeper insights on how undergraduate business students, who will soon be the decision makers and leaders to make "calculated risk" decisions, which are critical in our future society. The first part of the paper is to present a review on the cognitive processes in problem solving based on Polya's 4-phase framework of problem solving, Schoenfeld's six problem solving strategies, the Constructivist Theory and the Information Processing Model (IPM). Using Malaysian undergraduate business students as a case study, the second part of this paper is to propose a 7-step problem solving algorithmic model in a an attempt to improve the cognitive processes of students in solving MS problems and the quality of decision making.